Tantangan Dan Strategi Mempertahankan Nilai-Nilai Keberagamaan di kalangan Mahasiswa Universitas Islam Ahmad Dahlan - Wahyuningsih, Wahyuningsih; Badiana, Badiana; Fajaruddin, Fajaruddin; Muhsin, Muhsin (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This research seeks to investigate the challenges encountered by students in upholding religious values and to identify the strategies that can be employed to sustain these values in the face of modernity and globalization. This qualitative study adopts a phenomenological research design and employs a descriptive methodology to explore the challenges and strategies employed by students at Ahmad Dahlan Sinjai Islamic University in maintaining their religious values. Data collection techniques comprised observation, in-depth interviews, and documentation. The findings reveal that students encounter several challenges in upholding their religious values on campus, including social influences, academic pressures, divergent views and ideologies, lack of solidarity, and social media. The strategies adopted to mitigate these challenges encompass a holistic approach to strengthening religious education, cultivating sincerity and patience in academic pursuits, fostering Islamic solidarity, creating a conducive environment, engaging in religious studies, utilizing social media responsibly, and leveraging support and engagement from campus stakeholders and faculty members. This research aims to provide a substantial contribution to the enhancement of understanding regarding the maintenance of religious values among university students. Additionally, it is anticipated that policymakers will be able to develop more practical and applicable educational programs for students.